Periphery-Fused Chiral A2B-Type Subporphyrin - Shoma Hirokawa; Nagao Kobayashi; Soji Shimizu (Molecules, 2021)
Despite significant interest, the chiroptical properties of subporphyrins have rarely been investigated because chiral subporphyrins are elusive. Here, inherently chiral subporphyrins are elaborated by forming a fused pyran ring at the periphery of an A2B-type meso-aryl-substituted subporphyrin. Their circular dichroism (CD) properties are largely affected by the peripheral substituents and the dihedral angles between the meso-aryl substituents and the subporphyrin core: the β-perbromo subporphyrin with an orthogonal arrangement of the meso-phenyl substituents to the subporphyrin core exhibits weak CD signals corresponding to the Q bands, whereas the unsubstituted species with smaller dihedral angles shows relatively intense CD signals. A detailed structure–property relationship of these chiral subporphyrins was elucidated by time-dependent (TD) DFT calculations. This study reveals that the CD properties of chiral subporphyrins can be controlled by peripheral substitution and meso-aryl substituents.